Isolated Frontosphenoidal Craniosynostosis: The Alder Hey Experience and a Novel Algorithm to Aid Diagnosis. Issue 1 (January 2021) - Hennedige, Anusha; Bridle, Robyn; Richardson, David; Duncan, Christian; Parks, Christopher; Sinha, Ajay; Ellenbogen, Jonathan
Abstract : Abstract: Unilateral synostotic frontal plagiocephaly is most commonly due to a premature fusion of the frontoparietal suture. However, the coronal ring comprises of major and minor sutures and these sutures in isolation or in combination can result in similar clinical presentations which can make diagnosis challenging and result in a delay in referral to a craniofacial surgeon for timely management. Isolated frontosphenoidal craniosynostosis is a rare clinical entity with only 49 cases reported in the English literature to date. The authors present our series of 4 patients to add to this cohort of patients and describe key characteristics to distinguish frontoparietal from isolated frontosphenoidal synostosis and introduce a means of differentiating these 2 diagnoses from posterior deformational plagiocephaly and unilateral lambdoid synostosis. All previous case reports have been diagnosed after radiological imaging but the authors have devised a novel algorithm to aid the clinician in diagnosis of craniosynostosis before any radiological imaging.